Business Intelligence & Analytics Cost Accounting: Review and Synthesis of the Literature - Grytz, Raphael; Krohn-Grimberghe, Artus (Proceedings of the Pacific Asia Conference on Information Systems (2018))
Data driven decision-making using business intelligence and analytics (BI&A) is now standard in many companies and the importance of mitigating the accompanying growth in costs is thus increasing. Research shows that, while improved cost transparency for BI&A is important in practice, introducing systems is hampered by the gap of available methods and approaches in academic literature. To address this gap, we present a state-of-the-art examination of cost accounting of BI&A. By using a systematic literature review approach, we create an overview of this topic. We conclude that little research has been done on BI&A cost accounting and that it requires further work. There are, however, some approaches which could improve accounting within a BI&A architectural landscape. Our research helps clarify the key constructs we consider crucial for a BI&A cost accounting approach. We summarize our results and propose future research perspectives.